The Effectiveness of Youtube as an Online Learning Media - Rahmatika, Rahmatika; Yusuf, Munawir; Agung, Leo (Journal of Education Technology, 2021)
Covid-19 caused a transformation in the educational aspect. Teachers have difficulty implementing online learning. This is due to the lack of learning media that can facilitate students in learning. This study aims to analyze the effectiveness of Youtube as an online learning medium. This type of research is qualitative research. The method used in this research is qualitative research methods. The research subjects were three elementary school teachers. Data collection techniques in this study were interviews, observation, and documentation. The data analysis technique in this research is the analysis technique before being in the field and the analysis of the Miles and Huberman model. The result of this research is that Youtube can be used as a learning medium that helps students learn independently. Parents feel helped by YouTube learning media. Youtube can be accessed easily. In addition, Youtube learning media can be accessed anytime and anywhere so that parents can still accompany learning even though they are working. So it can be concluded that the YouTube learning media is effective in the online learning process. This research implies that Youtube can be used by teachers as a learning medium that can help students in learning. The selection of videos presented on Youtube must be adjusted to the material, age, and psychological development of students so that it makes it easier for students to understand the material presented on Youtube.